PEMANFAATAN SUMBERDAYA IKAN DI TAMAN NASIONAL KARIMUNJAWA: SUATU KAJIAN OPTIMASI PENANGKAPAN IKAN DAN BUDIDAYA LAUT - Yogi Yanuar; Budy Wiryawan; Sulaeman Martasuganda (Buletin PSP, 2008)
In order to support the sustainability of Karimunjawa National Park (KNP) especially for its function as a protected area, some regulations are needed through optimization of fishermen activities in KNP Traditional Fisheries Use Zone, i.e the determination of fish type, fishing season and number of fishing gears. The results show there are 4 (four) fish type that become fishermen’s major commodities : anchovies (Stolephorus spp.) with indeks value 3.16, frigate tuna (Auxis thazard) with indeks value 1.75, narrow-barred spanish mackerel (Scomberomerus commersoni) with indeks value 1.60, and yellowtail fussilier (Caesio cunning) with indeks value 1.05. Fishing season of anchovies occurs for 5 (five) months from June until October, frigate tuna occurs for 5 (five) months from August until December, narrow-barred spanish mackerel occurs for 5 (five) months from December until April and yellowtail fussilier occurs for 6 (six) months during February until May, September and October. The optimum number of fishing gears are (1) 81 units for Liftnet with anchovies as target fish, (2) 101 units for fish troll with frigate tuna and narrow-barred spanish mackerel as target fish, (3) 71 units for gillnet with yellowtail fussilier as target fish and (4) traps. Wider waters is needed to facilitate seaweed culture as alternative livelihood for local fishermen are 913 ha, with number of culture units needed by each fisherman are 3 units for floating fish cageculture based activities, 4 units for fish troll based activities with frigate tuna as target fish, 2 units for fish troll based activities with narrow-barred spanish mackerel as target fish, and 7 units for each repositioned fishermen, that are fishermen who has to completely change their activities to seaweed culturing.